(untitled) (Forseti. Law Review, 2025)
This article analyzes Expert Systems as part of Artificial Intelligence systems that seek to provide relevant input for decision-making. To this end, we refer to the case of Amauta Pro, which was recently developed by the Peruvian Judiciary, to explain its characteristics, benefits, limitations, success criteria, and opportunities for improvement in its implementation.